2010
DOI: 10.1111/j.1749-7345.2009.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Risk of Ciguatera Fish Poisoning from Reef Fish Grown at Marine Aquaculture Facilities in Hawai'i

Abstract: Fish grown in open ocean aquaculture facilities from two commercial farms in Hawai'i were assessed for the presence of the marine toxin ciguatoxin. Facilities were surveyed for the presence of the marine benthic dinoflagellate, Gambierdiscus spp., which is known to produce the toxin. The dinoflagellate was detected in three submerged open ocean cages operated by Hukilau Foods (formerly known as Cates International Inc.) and one open ocean cage operated by Kona Blue Water Farms at relatively low levels averagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A CIEA format enabled a LOD of approximately 5 pg mL −1 of equivalent CTX per mg of extract (corresponding to 5 × 10 −12 M), which lies in the range of the neuroblatoma cell assay. Moreover, the CIEA yielded consistent results when compared to this assay using flesh extract of fish caught in natura or raised in aquaculture farm [ 149 , 150 ].…”
Section: Methodologies For Ctxs Determinationmentioning
confidence: 94%
See 1 more Smart Citation
“…A CIEA format enabled a LOD of approximately 5 pg mL −1 of equivalent CTX per mg of extract (corresponding to 5 × 10 −12 M), which lies in the range of the neuroblatoma cell assay. Moreover, the CIEA yielded consistent results when compared to this assay using flesh extract of fish caught in natura or raised in aquaculture farm [ 149 , 150 ].…”
Section: Methodologies For Ctxs Determinationmentioning
confidence: 94%
“…For instance, RBA values for CTX toxicity determination correlated well with those obtained using an analytical approach, MBA or CBA [ 4 , 146 148 ]. A comparative study between enzyme-linked immunoassay (ELISA) and CBA also indicated a high correlation between both methods [ 149 , 150 ]. The same remark applies to CTX determination using CBA in parallel with LC-MS/MS analysis [ 119 , 151 ].…”
Section: Methodologies For Ctxs Determinationmentioning
confidence: 99%
“…Large carnivorous finfish, such as amberjack, snapper, grouper, and mackerel, which live in shallow tropical and subtropical waters, can accumulate CTX (Friedman et al., 2017). Around 4% of finfish from the U.S. Virgin Islands (Loeffler et al., 2018) and 7.4% of wild‐captured kahala fish from Hawaii (Campora et al., 2010) had CTX levels that exceeded the FDA action level. The CTX toxicity and profile were not significantly different between frozen and cooked finfish (Abraham et al., 2012).…”
Section: Major Safety and Quality Concerns/issuesmentioning
confidence: 99%
“…When analyzing flesh fish, the most commonly used protocol for toxin extraction is a modification of that for MBA [ 91 ]. All protocols are based in acetone extraction, followed by evaporation and two solvent partitions with methanol:water and hexane, and ethanol:water and diethyl ether, to remove fatty acid and polar compounds [ 103 , 151 , 152 , 153 ]. Additional steps with solid-phase extraction (SPE) cartridges can be also performed for further purification [ 154 ] or instead solvent partition for rapidity [ 155 , 156 ].…”
Section: Biosensors Biochemical Assays and Cell-based Assaysmentioning
confidence: 99%